Reputational scores and dignity in the digital society - di Carpegna Brivio, Elena (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
The paper analyzes how algorithmic reputational scores can influence human personality. They make it possible to instantly establish rankings that shape individuals behavior, creating forms of subjection, exclusion, or privilege. The concept of dignity, present in numerous Constitutions and Charters of Rights, can counter this drift and link social recognition to the free unfolding of each person’s personality.